2018
DOI: 10.1111/ajag.12580
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of dementia in residential aged care settings in Australia: An opportunity for improvements in quality of care?

Abstract: There may be a lack of formal diagnosis of dementia in Australian RACFs. Greater efforts from all health professionals to improve diagnosis in this setting are required. This is an opportunity for improved person-centred care and quality of care in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
3
17
1
1
Order By: Relevance
“…Our results suggest that ACFI data alone may generally underestimate condition prevalence, but the magnitude of underestimation varies by condition. Consistent with prior research, dementia can be reasonably well identified from ACFI data(18), but we suspect that dementia may still be underdiagnosed and underreported in this setting as previous research has shown (19). This trend in underreporting of conditions is supported by condition prevalence reported in Aged Care Assessment Program (ACAP) data(16) (an assessment conducted before RACF admission -i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Our results suggest that ACFI data alone may generally underestimate condition prevalence, but the magnitude of underestimation varies by condition. Consistent with prior research, dementia can be reasonably well identified from ACFI data(18), but we suspect that dementia may still be underdiagnosed and underreported in this setting as previous research has shown (19). This trend in underreporting of conditions is supported by condition prevalence reported in Aged Care Assessment Program (ACAP) data(16) (an assessment conducted before RACF admission -i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Our results suggest that ACFI data alone may generally underestimate condition prevalence, but the magnitude of underestimation varies by condition. Consistent with prior research, dementia can be reasonably well identi ed from ACFI data(22), but we suspect that dementia may still be underdiagnosed and underreported in this setting as previous research has shown (23). This trend in underreporting of conditions is supported by condition prevalence reported in Aged Care Assessment Program (ACAP) data(20) (an assessment conducted before RACF admission -i.e.…”
Section: Discussionsupporting
confidence: 86%
“…Providing high quality care for people living with dementia is complex (Dyer et al, 2018) and the poor quality of care currently being provided in care homes has been raised as a concern (e.g. Cadigan et al, 2012;Pot et al, 2013).…”
Section: Benefits Challenges and Best Practicesmentioning
confidence: 99%